Identifying Critical Barriers And Drivers For Green Supply Chain Management Application In The Malaysian Construction Industry - Heng, Yong Ming (2018)
The construction industry is a major contributor to both global pollutions and global warming. Booming construction activities consume large amount of natural resources and cause degradation of ecology, eventually result in an adverse impact to our earth, human beings, natural environment and other living creatures. Devastating floods, annual dry spells, irregular weather patterns as well as unpredictable storms have become major concerns in Malaysia. Green Supply Chain Management (GSCM), which is the integration of environmental thinking into the supply chain management has started to gain attention from many parties as they are increasingly aware of the global pollution issues.